Phytochemical screening and In-vitro antioxidant activity of Centella asiatica extracts - Mukesh Kumar Yadav; Santosh Kumar Singh; JS Tripathi; YB Tripathi (International Journal of Phytomedicine, 2017)
Centella asiatica also known as mandukparni or Indian pennywort or jalbrahmi, which has been used as a medicine in the Ayurveda from ancient times and mentioned in many classical texts of Ayurveda. Centella asiatica has long been used to improve memory and cognitive function. The study aimed to identify the phytochemicals present in different solvent extracts of Centella asiatica (i.e. PECA- Petroleum ether extract of C. asiatica, CCA- Chloroform extract of C. asiatica, EACA- Ethyl acetate extract of C. asiatica, ECA- Ethanolic extract of C. asiatica, HACA- Hydro-alcoholic extract of C. asiatica) and evaluate the respective in-vitro antioxidant potentials. The phytochemical screening of extracts was done with standardized procedures and the antioxidant potential of different solvent extracts of Centella asiatica was assessed by its free radical scavenging activity 2, 2-diphenyl -1- picrylhydrazyl (DPPH) as well as hydrogen peroxide scavenging assay respectively for reducing capability. In all different solvent extracts of C. asiatica revealed excellent free radical scavenging activity as revealed by 2-2- diphenyl-1-picryl-hydrazyl (DPPH) assay with EC50 values for ECA=128.752±1.85 μg/ml, HACA=274.884±1.21 μg/ml and hydrogen peroxide assay against the standard (Butylated hydroxytoluene) BHT, with the EC50 values ECA=429.69±0.92 μg/ml HACA=458.08±0.58 μg/ml while rest solvent extracts shown very less antioxidant activity. The present study indicates that the Centella asiatica extracts have good antioxidant activity which can be used in stress and anxiety and also a good source to be used as natural drugs.